Impact of Globalization on Indian Culture - Rasool Raina, Aasif (International Journal of Psychosocial Rehabilitation, 2020)
The impact of Globalization can be tracked by examining the various trends of the social and cultural patterns during the early stages and as of today. The Era of Globalization is fast becoming the preferred term for describing the current times. The vigour of the renewed sense of self-awareness generated among the members of the local cultures and communities is such as to succeed in making adaptive reconciliation with the forces of globalization. The linkages both visible and invisible, defining the cultural interdependence among communities and regions in India which have existed historically, reinforce instead of threatening the national identity. The impact of globalization is great on India’s culture. We are exploiting the term globalization in the name of reason, progress and science but we are forgetting that it is our culture that differentiates us from any other country. India has a rich cultural background and pride of its culture is famous in all over world. Globalization has not only inculcated the westernization in India, but conversely the Indian culture has also spread its impact globally.